Application of rubber dam in restorative and endodontic procedures: The experience of the therapist and the patient - Stašić Jovana N.; Ilić Jugoslav; Savić-Stanković Tatjana (Stomatološki glasnik Srbije)
Introduction/Objective Challenges in the application of the rubber dam, inexperience, and discomfort of the patient are reasons for its undesirability. That is why education and training of young dentists is important, as well as bringing this phase of work closer to patients in order to reduce discomfort. The objective was to examine the attitudes about knowledge and skills of young dentists in our community and the impression of patients during the application of the rubber dam in the performance of restorative and endodontics procedures. Methods The research was conducted on the basis of epidemiological questionnaires filled out by 30 dentists (specialist studies and internship at the Clinic for Dental Diseases) and 30 patients immediately after working with the rubber dam. The questionnaires had three categories: general information about the dentist's knowledge and experience, information on clinical work with the rubber dam, and patient impressions. Results A total of 37% of dentists had the experience of using rubber dam during endodontic procedures, while 23% of dentists used them during restorative procedures. Lack of experience (2-4 years) did not significantly affect the ability to place rubber dam in simple clinical procedures (p = 0.321) while it had a significant impact in more difficult situations (p = 0.027). During clinical work, the indication for the placement of the rubber dam did not significantly influence the choice of the jaw on which the dental procedure will be performed (p = 0.659). The average time for placing the rubber dam in both procedures was five minutes. After clinical work, 57% of patients felt no pain, and 93% would agree to reapply the rubber dam during future procedures. Conclusion Young dentists have knowledge but insufficient experience when working with the rubber dam, which can be explained by their caution with the analysis of the clinical situation. Additional education and training during work with the rubber dam is necessary, in order to increase the independence of young dentists. Patients easily tolerate working with rubber dam and have a positive opinion.